2017
DOI: 10.1111/neup.12391
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory dysfunction in the APP/PS1 transgenic mouse model of Alzheimer's disease: Morphological evaluations from the nose to the brain

Abstract: Olfactory dysfunction is among the signs of Alzheimer's disease (AD) and cognitive impairment. It has been demonstrated Aβ was associated with olfactory impairment observed in both transgenic mice and in AD patients. In this study, we evaluated amyloid deposition in the olfactory circuit of APP/PS1 transgenic mouse model of AD, which showed olfactory dysfunction in olfactory behavior tests. We found amyloid depositions were widely distributed in the whole olfactory circuit. Moreover, we think these amyloid dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 39 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…These alterations are reflected in population activity changes, which seem to underlie cognitive deterioration and other related symptoms in AD [8, 9, 1216]. Similar alterations in network activity have been observed in the OB upon the acute or prolonged presence of oligomerized A β [1719], which also induces alterations in olfaction [1721]. Considering that various OB oscillatory activities have been closely linked to olfactory information processing [2228], it is likely that the A β -induced alterations in OB activity contribute to olfactory dysfunction.…”
Section: Introductionmentioning
confidence: 90%
“…These alterations are reflected in population activity changes, which seem to underlie cognitive deterioration and other related symptoms in AD [8, 9, 1216]. Similar alterations in network activity have been observed in the OB upon the acute or prolonged presence of oligomerized A β [1719], which also induces alterations in olfaction [1721]. Considering that various OB oscillatory activities have been closely linked to olfactory information processing [2228], it is likely that the A β -induced alterations in OB activity contribute to olfactory dysfunction.…”
Section: Introductionmentioning
confidence: 90%
“…By analyzing Figures 6B,C , it is possible to clearly observe the OE inner structure [i.e., olfactory neurons layer (2) laying on connective tissue (1) with altered blood vessels (4)] and allowed thickness measurement of the tissue samples (≈ 100 vs. ≈ 140 μm for histological examination). Note that observations were more challenging due to the fact that the OE seems “crumbly,” possibly because of the older mice which lead to increase the number of Amyloid-β deposits and senile plaques as demonstrated in Wu et al ( 2013 ) and Yao et al ( 2017 ). Presumed amyloid-β peptides could be detected if we considered the very high brightness (compared to the rest of the tissues) spots (white arrows in Figure 6C ), possibly due to the presence of anti-Amyloide-β primary antibody revealed with fluorescent secondary antibody.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, in AD, odor detection, discrimination and identification are affected earlier than cognitive performances as demonstrated in several studies on patients (Talamo et al, 1991 ; Arnold et al, 1998 ; Wang et al, 2010 ), as well as on different animal models, in particular mice (Sohrabi et al, 2012 ; Alvarado-Martínez et al, 2013 ; Wu et al, 2013 ). These functional olfactory alterations are probably due to early Amyloid-β peptide deposits in the olfactory epithelium (OE) leading to cellular apoptosis and a decrease of dendritic spine densities (Yao et al, 2017 ). These studies have identified a need to investigate, in a more advanced manner, the area of the nasal cavity which concentrates part of the olfactory functionalities in order to establish reliable biomarkers of AD.…”
Section: Introductionmentioning
confidence: 99%
“…A correlation between olfactory dysfunction and amyloid deposition was reported in APP/PS1 mice ( 43 ). Transgenic mice with selective overexpressing humanized APP (hAPP) in either mature or immature OSNs exhibited widespread cell-autonomous apoptosis in OSNs, exhibiting that Aβ pathology is involved in olfactory neurodegeneration ( 44 ).…”
Section: Mechanisms Of the Olfactory Pathophysiology In Admentioning
confidence: 90%